Managing Chinese employees: dialogues from the notion of self - Cheung, Lai Wan (2011)
This thesis explores cross-cultural management from an employee's perspective. It investigates how Chinese employees make sense of their selves in relation to their expatriate managers and to their work in multinational companies (MNCs).